EFECTO FOTOPROTECTOR DE Macrocystis pyrifera FRENTE A BLOQUEADORES SOLARES EN LA PREVENCIÓN DE LESIONES DE PIEL - Castro, Américo J. (2015)
Objective of the study was to compare the sunscreen effect in vivo of a cream made with the hydroalcoholic extract of the brown seaweed Macrocystis pyrifera (Linnapus) Agardh, with comercial sunscreens in skin lesions prevention. The biological sample was collected in the continental socket from Yanyarina beach, San Juan de Marcona, Ica region. Hydroalcoholic extract (ethanol 1:1) was obtained for maceration process since 300 g seaweed. With the extract was formulated and design the blocker dermocosmetic using concentrations of 5, 10, and 15%, respectively, with a mixture of solids aliphatic alcohols, consisting mainly of Cetyl alcohol (C16H3O) and Stearyl alcohol (C18H39O) 50/70%. Were used albino mice, mus musculus specie, bald c53 strain, adult males, with average weight 30 g. Photoprotective potential in vivo was tested through topical application on mice skin, in the dorsal anterior third of loin. The animals were distributed into seven groups of five. Group 1 (white) was not applied cream or irradiation UV-B 320 ŋm; Group 2 (control) was not applied cream and was irradiated with UV-B light; groups 3 and 4 were treated with commercial sunscreens and irradiated with UV-B light; groups 5, 6 and 7 (intervention) were applied the processed product and were irradiated them with UV-B. The sunscreen effect was evident in macroscopic and microscopic analysis of skin. In the microscopic analysis, group 1 presented skin with preserved structure; groups 2, 3 and 4; had altered structure; while group 5 presented slight alteration, group 6, structure seemingly normal and group 7 structure normal. It was concluded that the hydroalcoholic extract exerts sunscreen effect in vivo against UV-B irradiation on worked concentrations; achieving more protection when is used a major extract concentration, this was evidenced because the skin structure looks less altered with dermis and epidermis, layer corneal lamellar and basal apparently normal.